Application of Transition Theory in Becoming Teenage Parents - Sriyasak, Atcharawadee; Chookanhom, Phatcharee; Sridawrung, Chaweewan (Journal of The Royal Thai Army Nurses, 2020)
The birth of a child brings about major changes in a family. It can trigger a family crisis or even a life crisis for a first-time parent who is adapting to the new role. The transition to parenthood is more difficult for teenage parents, who face difficulties with adapting to child care as well as with balancing parenting and work. They have to balance between the parent role and teenage role as the same time. Teenage parenthood is a developmental and situational transition. Nursing are interested in transition to parenthood due to they work close to the family. Families play a strong role in the development of children’s health. Nurses can apply transition theory by analysis and nursing care plan. By doing this, will help the teenagers becoming a parent smoothly.